Understanding leadership practice in a Lebanese school : a director's experience - Hamadeh, Nabila Zawkan (Beirut American University of Beirut - Faculty of Arts and Sciences - Department of Education, 2006)
The purpose of the study is to examine and understand leadership practice from t he perspective of one division director of a Lebanese school. The conceptual fra mework is based on Bolman and Deal's Four Frames model of leadership: structural , human resource, political, and the symbolic frame. Bolman and Deal assert that leaders can reach a deeper and better understanding of organizations and be mor e effective when they are able to respond to the needs of their organizations fr om more than one frame. As a graduate student in the field of educational administration and leadership, the question of how to practice educational leadership in a school setting in L ebanon is important to me. I became interested in the leadership process and the meaning that school leaders give to events and actions that occur in this conte xt. I used qualitative research strategies. Data were collected through audio-taped interviews, observations and shadowing, and review of key documents. A categoriz ing strategy was adapted to analyze data, and to answer three research questions focusing on the director's practice, the frames that shape her experience, and the impact of framing on her practice. The findings indicate that the director's practice involves a significant amount of duties and responsibilities, viewed t hrough a combination of structural and human resource frames. The political and symbolic frames were most used in times of conflict, tension, and ambiguity. Mor eover, the director demonstrated a framing perspective that is not limited to ju st one or more of Bolman and Deal's four frames. In addition to framing concepts based on Bolman and Deal's model of leadership, emerging themes appeared to inf luence the director's practice. They consisted of skills, physical characteristi cs, symbolic tools, and concepts used according to the requirements of the situa tion. The study represents an attempt to understand and bridge the gap between c onceptual thinking and real-life situations and events in the context of school leadership.
: Mémoire
Keywords: Administration Scolaire; Educational administration; Leadership; Leadership